2019
DOI: 10.35424/rcar.v5i98.140
|View full text |Cite
|
Sign up to set email alerts
|

Análise da Evolução Temporal do Datum Vertical Brasileiro de Imbituba

Abstract: Actualmente, los temas más centrales de Geodesia se vinculan a la provisión de un Sistema de Referencia Global único, al que puedan vincularse de forma unívoca y con exactitud los cambios globales de carácter geométrico y físico. El Global Geodetic Reference Frame tiene como objetivo la mejor estructuración de los Sistemas de Observación de la Tierra actualmente con perspectivas de la determinación de los cambios globales al nivel de una parte por mil millones, considerando varios parámetros geométricos y físi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0
12

Year Published

2019
2019
2021
2021

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(19 citation statements)
references
References 3 publications
(5 reference statements)
0
7
0
12
Order By: Relevance
“…In 1997, the Federal University of Paraná, together with the Brazilian Institute of Geography and Statistics (in Portuguese IBGE), started with different multiparametric campaigns in the datum area, that was carried out over the years. These include GPS positioning, atmospheric pressure monitoring, earth and ocean tides, as well as the recovery of historical altimetric references, tide gauge station reactivation, gravimetry and geodetic observations densification in the contiguous region involving the Imaruí Lagoon system and the search for the link between B-FVN and IHRS [8,17,18,[20][21][22][23][24][25].…”
Section: Study Area and Data Sets 21 Imbituba Brazilian Vertical Datummentioning
confidence: 99%
See 4 more Smart Citations
“…In 1997, the Federal University of Paraná, together with the Brazilian Institute of Geography and Statistics (in Portuguese IBGE), started with different multiparametric campaigns in the datum area, that was carried out over the years. These include GPS positioning, atmospheric pressure monitoring, earth and ocean tides, as well as the recovery of historical altimetric references, tide gauge station reactivation, gravimetry and geodetic observations densification in the contiguous region involving the Imaruí Lagoon system and the search for the link between B-FVN and IHRS [8,17,18,[20][21][22][23][24][25].…”
Section: Study Area and Data Sets 21 Imbituba Brazilian Vertical Datummentioning
confidence: 99%
“…Palmeiro et al showed that the association of local gravimetric geoids with the intended global geoid involves a series of associated problems [12]. These are the consequences of the different reference levels (RLs) involved in addition to the resolutions of the various used databases, as can be seen in [25].…”
Section: Study Area and Data Sets 21 Imbituba Brazilian Vertical Datummentioning
confidence: 99%
See 3 more Smart Citations